Overview of Alumni Behavior And The Impact Of Public Speaking Training On Health Human Resources In The Ministry of Health A Quantitative Study at the Ciloto Health Training Center (BBPK Ciloto), Ministry of Health of Indonesia - Bastaman, Rudi (International Journal of Science, Technology & Management, 2025)
The background of this study lies in the relatively low public speaking ability among health human resources in Indonesia. Public speaking is one of the essential skills required across various aspects of life organizational, academic, professional, and social. Individuals with strong public speaking skills are also needed in health service institutions or organizations. Public Speaking Training for Health Human Resources aims to develop competencies that equip health human resources with the ability to speak effectively in public. To ensure that such training is well-organized, high-quality, and effective, a Post-Training Evaluation is conducted. This Post Training Evaluation aims to assess the effects of public speaking training on behavioral changes among alumni and its impact in their workplaces. The study employs a descriptive quantitative approach with total sampling of 60 alumni from two cohorts Public Speaking Training Batch 2023 and Batch 2024. Data were collected online using a Google Form questionnaire. The evaluation results show that all participants have applied the training material in their daily work following the standard structure of public speaking : introduction, body, and conclusion. Most alumni reported increased confidence when speaking in public. Public Speaking Training for Health Human Resources has proven effective in fostering behavioral change and improving workplace performance. Respondents stated that the training materials were relevant to their job needs and applicable in various public speaking activities, such as being a resource person, facilitator, conducting socialization sessions, and participating in meetings.